New Global Studies (De Gruyter, 2007)
New Global Studies approaches contemporary globalization as a whole and across disciplinary lines. It draws from history, sociology, anthropology, political science and international relations to study the past and present of today's globalizing process. Topics include economic globalization, global media networks, preservation of the global environment, transnational manifestations of culture and the methodology of global studies itself.